Study of various diameter and functionality of TEMPO-oxidized cellulose nanofibers on paraquat adsorptions - Huang, Chih-Feng; Tu, Cheng-Wei; Lee, Rong-Ho; Yang, Cheng-Han; Hung, Wei-Chen; Andrew Lin, Kun-Yi (Polymer degradation and stability, 2019)
The adsorption of paraquat was examined in the presence of renewable nanomaterials of 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) oxidized cellulose nanofibers (TOCNs) with different oxidation time (i.e. TOCN-1h, TOCN-4h, TOCN-8h, and TOCN-24h). First, we monitored the relationships among TEMPO-mediated oxidation times, cellulose surface functional groups, and fiber diameters. We observed the oxidation and the carboxylate contents of cellulose were promptly increased in an hour, leading to the formation of nano-sized cellulose fibers (ca. 20 nm). These cellulose nanofibers were characterized by Fourier-transform infrared (FT-IR), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) method, and wide angle X-ray diffraction (WAXRD). Accordingly, the TOCNs with enlarged specific surface area (ca. 180 m2/g) performed high adsorption efficiency for paraquat (>90%), contributing from the strong attraction force between carboxylate anion on TOCNs and parquet cation. The adsorption behaviors were revealed by intra-particle diffusion (IPD) model. For TOCN-24 h, IPD of adsorbate from the surface to the active sites within the hemicellulose or disorder region was observed, resulting in the increase of the adsorption equilibrium time. We then comprehended the absorption performance was sensitive under different pH environments. The adsorption capacity over 100 mg/g can be reached at a pH value greater or equal to 7. Furthermore, Langmuir isotherm model was fitted to the adsorption behaviors at various temperatures, indicating a single layer adsorption mechanism. [Display omitted] •Highly efficient to obtain TEMPO-oxidation cellulose nanofibers (TOCNs) that obtain high carboxylate content and degree of oxidation.•Controllable diameters and functionality of nanocelluloses and largest specific surface area of and remain high crystallinity index.•High maximum adsorption property compared to ZSM-5 and active carbon adsorbents were achieved. TOCNs can effectively adsorb paraquat cations when the pH value is greater or equal to 7.0.•Importantly, we found Langmuir model (i.e. a single layer adsorption) was fitted to explain the adsorption behaviors.